2014
DOI: 10.2174/156720501108140910114230
|View full text |Cite
|
Sign up to set email alerts
|

The Alzheimer’s Disease-Related Glucose Metabolic Brain Pattern

Abstract: The Alzheimer's disease-related cerebral glucose metabolic covariance pattern identified by SSM/PCA analysis was highly sensitive and specific for Alzheimer's disease. This method is expected to be helpful in the early diagnosis of Alzheimer's disease in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
48
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 0 publications
10
48
1
1
Order By: Relevance
“…We and others have used 18 F-fluorodeoxyglucose (FDG)-PET and fMRI to identify diseasespecific networks in PD, AD, Huntington disease, and other conditions. [7][8][9][10][11][12][13] We have shown that akinesia-rigidity in PD correlates with the expression of a PD motor-related pattern (PDRP) 10,11 such that more severe symptoms are reflected in higher PDRP scores; tremor is mediated by a distinct cerebello-thalamocortical network 14 ; and the expression of a distinct PD cognition-related pattern (PDCP), characterized by diminished metabolism in the medial frontal and parietal regions, rises as cognitive function deteriorates. [15][16][17][18] Similarly, in AD, neuropsychological test performance correlates with the expression of an AD-related pattern (ADRP) characterized by covarying reductions in hippocampal, superior temporal, and parieto-occipital resting-state activity.…”
mentioning
confidence: 99%
“…We and others have used 18 F-fluorodeoxyglucose (FDG)-PET and fMRI to identify diseasespecific networks in PD, AD, Huntington disease, and other conditions. [7][8][9][10][11][12][13] We have shown that akinesia-rigidity in PD correlates with the expression of a PD motor-related pattern (PDRP) 10,11 such that more severe symptoms are reflected in higher PDRP scores; tremor is mediated by a distinct cerebello-thalamocortical network 14 ; and the expression of a distinct PD cognition-related pattern (PDCP), characterized by diminished metabolism in the medial frontal and parietal regions, rises as cognitive function deteriorates. [15][16][17][18] Similarly, in AD, neuropsychological test performance correlates with the expression of an AD-related pattern (ADRP) characterized by covarying reductions in hippocampal, superior temporal, and parieto-occipital resting-state activity.…”
mentioning
confidence: 99%
“…The so-called metabolic networks of the brain are acquired in a similar manner to fMRI-derived networks, namely by analyzing temporal [ 155 ]. Such metabolic networks were recently constructed for PD [ 156 ] and AD [ 157 ]. Structural brain networks represent physical connections between brain regions by white matter fi ber tracts.…”
Section: Disease-specifi C Brain Networkmentioning
confidence: 99%
“…AD is characterized pathologically by accumulation of amyloid -peptiderich senile plaques, neurofibrillary tangles [composed of aggregated hyperphosphorylated tau], and loss of synapses. A major clinical sign of AD is decreased glucose utilization in temporoparietal and other brain regions (Teune et al, 2014). Type 2 diabetes mellitus (T2DM) is a major risk factor for development of AD, and brains from subjects with AD and T2DM have elevated indices of oxidative and nitrosative stress (Hoyer, 2002;Craft et al, 2005;de Felice, 2013;de la Monte, 2009;Calvo-Ochoa et al, 2015;Butterfield et al, 2014b).…”
Section: Accepted Manuscriptmentioning
confidence: 99%